SHAPE SELECTIVITY OF AND SYNTHETIC VISUAL INTELLIGENCE - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The process of coding information for face recognition in human is largely remaining unknown. In this study, we carry out few experiments to determine the factors influencing coding mechanism in parahippocampal place area of the brain. The results show some significant outcome toward the shape selectivity of the brain and latter we construct a computational mechanism to mimic the coding features behind face recognition.